2014
DOI: 10.1158/1078-0432.ccr-14-0149
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA Mutational Status in Circulating Tumor Cells Can Change During Disease Recurrence or Progression in Patients with Breast Cancer

Abstract: Purpose: Molecular characterization of circulating tumor cells (CTC) is crucial for the investigation of molecular-targeted therapies while PIK3CA somatic mutations play a crucial role in therapy response. We investigated the presence of PIK3CA mutations in CTC and whether this is associated with clinical outcome.Experimental Design: We developed and validated an ultrasensitive methodology for the detection of PIK3CA mutations that is based on a combination of allele-specific, asymmetric rapid PCR and melting … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 54 publications
3
55
1
Order By: Relevance
“…Other studies have also detected PIK3CA mutations in CTCs and DTCs that were not found in their corresponding primary tumors. 5254 …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also detected PIK3CA mutations in CTCs and DTCs that were not found in their corresponding primary tumors. 5254 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the molecular analysis of CTCs is anticipated to (a) reveal new therapeutic targets, (b) delineate cancer cell signaling, and (c) explore cancer cell dissemination. Such molecular characterization of CTCs has focused on the gene expression [70][71][72] , DNA methylation [73,74] , as well as DNA mutation levels [75,76] . Currently, there are many large-scale translational studies in progress, which will generate critical data and drive CTC analysis and implementation in the clinic, empowering tailor-made therapeutic strategies [77] .…”
Section: A Complementary Role For Liquid Biopsies (And In Particularmentioning
confidence: 99%
“…PIK3CAm have been detected in CTCs from patients with both early and metastatic breast cancer [21,22]. Despite implementing different methodologies, two studies demonstrated the dynamic nature of the mutation with loss or gain of PIK3CAm detected as tumors progress or recur.…”
Section: Pik3ca Mutations In Breast Cancermentioning
confidence: 99%